Cross-cultural adaptation of the Arabic version of the Disability Rating Scale among caregivers of patients with traumatic brain injury - Alqahtani, Abdulaziz; Seyam, Mohamed K.; Kashoo, Faizan; Alqahtani, Mazen; Abu Shaphe, Mohammad; Moubarak, Ezzat; Shawky, Ghada; Nambi, Gopal; Chahal, Aksh; Ahmad, Mehrunnisha (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. The Disability Rating Scale (DRS) is a short, eﬃcient, rapid instrument for monitoring general functional recov-ery from moderate to severe traumatic brain injury (TBI). The 8-item DRS is a published and validated assessment instrument but has not yet been adapted to native Arabic-speaking caregivers of patients with TBI. This study aimed to translate, cross-culturally adapt, and test the reliability of the Arabic version of the DRS.Methods. Cross-cultural adaptation and translation were performed according to the recommended guidelines: translation, back-translation, expert review, and pretesting. Reliability was assessed via a test-retest procedure at 2-week intervals using the Kappa coeﬃcient among 42 caregivers of patients with TBI.Results. The agreement among the raters was excellent, varying from 0.88 to 1. Translating the DRS into Arabic was easy based on the translators’ information. The test-retest reliability was excellent (interclass correlation coeﬃcient = 0.99 with a 95% CI 0.998 to 0.999 [F(41) = 1100.7, p < 0.001]. The Cronbach’s alpha for the internal consistency of the DRS was 0.917. There was good agreement (convergent validity) between the DRS scores with the Short Form 36 Health Survey Questionnaire [rs(42) = 0.895, p = 0.001].Conclusions. The Arabic version of the DRS can be used among Arabic-speaking caregivers of patients with TBI. The Arabic translated version of the DRS can be used among caregivers of patients with TBI telephonically by expert professional. The translated questionnaire was easy to comprehend among caregivers of patients with TBI, with excellent test re-test reliability and good convergent validity.
Keywords: traumatic brain injury; Arabic; translation; reliability; cultural adaptation; questionnaire; validation